Assessing the Relationship Between Groundwater Dynamics and Land Subsidence Using Time-Series SAR Data - Yehia Miky (Civil Engineering Journal, 2026)
Groundwater is considered as the primary source of drinking and agricultural supply for most residents in Mecca region. However, data indicates that groundwater restore is substantially lower than the consumption rate, which results in a reduction in the quality of water and decline in groundwater levels. This, in turn, has resulted in surface subsidence, causing problems in infrastructure. The main aim of this research is to assess the correlation between groundwater dynamics and surface subsidence in the Mecca region using time-series SAR imagery. So, time series maps of land subsidence, along with the spatial distribution of long-term subsidence from 2016 to 2025, were generated. The results indicate that the basin experienced an average deformation velocity of less than 4 cm/year, with maximum subsidence reaching 15.2 cm in highly compressible soils. The analysis further shows that land subsidence generally increases with higher groundwater extraction rates. However, only two soil types (the Abbasah Formation and the diorite–pyroxenite unit) exhibited a substantial positive correlation between groundwater flow rate and subsidence (R2 = 0.67). Quantitative analysis of the correlation helps water managers to take the necessary actions, such as identifying crop types, and irrigation methods, to preserve and sustain the Kingdom's water resources.